Aging Men's Health-Related Behaviors. (4th November 2014) - Peak, Terry; Gast, Julie A.
This conceptual review summarizes the current research on older men and their health-related behaviors with special attention given to the influence of the hegemonic masculinity framework over the life span. The authors consider whether masculinity precepts can be modified to enable men to alter their gendered morbidity/mortality factors and achieve healthier and longer lives. Also included is an overview of the gender-based research and health education efforts to persuade men to adopt more effective health-related behaviors or health practices earlier in the life span. Given the current attention being paid to men's health, for example, their higher risk of morbidity and mortality both generally and at younger ages, and the associated health care costs tied to those risks, the ethical and economic implications of this review may prove useful.